Effects of Strengths of Steel and Concrete, Eccentricity and Bar Size on the Optimization of Eccentrically Loaded Footings - Yeh, Jiin-Po; Huang, Kuan-Hao (Transactions on Engineering and Computing Sciences, 2017)
This paper aims to explore effects of the yield strength of steel, compressive strength of concrete, eccentricity of the axial load and steel bar size on the optimization of reinforced concrete isolated footings. The optimization tool adopted in this paper is genetic algorithms. Based on the ACI Building Code, constraints are built by considering the wide-beam and punching shears, bending moment, upper and lower limits of reinforcement, allowable soil pressure, development length for deformed bars and clear distance between parallel deformed bars. Design variables consist of the width, length and thickness of the footing and the number of bars in the long and short directions, all of which are integers. The objective is to minimize the cost of steel and concrete used in the footing. By changing one of the four factors: the yield strength of steel, compressive strength of concrete, eccentricity and bar size while fixing the other three, this paper finds that the highest yield strength of steel, the lowest compressive strength of concrete, the smallest eccentricity and No. 6 bar, respectively, will lead to the optimal results. In addition, when the size of the reinforcement gets larger, the optimal footing have a tendency to become square and thicker.